Sports nutrition - From lab to kitchen (Meyer & Meyer Sport (UK) Ltd., 2018)
This book is unique in that it is a book written by world experts in a way that can easily be understood by athletes and which can immediately result in changes that can help performance or recovery. The various chapters are written by leaders in the field who discuss the latest science and translate the scientific findings into a practical message. So it is not just theory, every chapter contains clear advice and by doing so this book bridges the gap between science and practice. After reading this book, athletes and coaches will be up to date with the latest developments, will be able to distinguish fact from fiction and will be able to make changes to their nutritional preparation that will have an impact. Klappentext